(untitled) (Anwer Khan Modern Medical College Journal, 2012)
Non-High density lipoprotein cholesterol reflects total cholesterol minus HDL cholesterol and encompasses all cholesterol present in potentially atherogenic lipoprotein particles. It has been recently suggested that Non-HDL cholesterol might be a useful marker and a better predictor of atherosclerosis in type 2 diabetic subjects. The study was designed to explore the role of non- HDL cholesterol in diabetic population. It was a case-control study. 150 subjects irrespective of sex were selected. Of them 103 were diabetic and 47 were non-diabetic. The lipid profile including total cholesterol, TG and HDL-C were measured following standard method & procedure. LDL-C was calculated using Friedwald’s formula. TG concentration of >400 mg/dl were excluded from the study. Non HDL-C is calculated by subtracting the level of HDL cholesterol from total cholesterol. Unpaired t test and chi square test were done to find out the level of significance. Non-HDL cholesterol was compared between the study groups and significant differences were observed (p value <0.001). Non-HDL cholesterol is elevated in type 2 diabetes mellitus and therefore should perform as a routine assessment in all diabetic subjects. DOI: http://dx.doi.org/10.3329/akmmcj.v3i2.11688 AKMMC J 2012: 3(2): 15-18